Factors associated with media use for parenting information: A cross‐sectional study among parents of children aged 0-8 years - Irene N. Fierloos; Dafna A. Windhorst; Yuan Fang; Yuping Mao; Matty R. Crone; Clemens M.H. Hosman; Wilma Jansen; Hein Raat (Wiley, 2022)
Abstract Aim Media use may strengthen parents' capacities to deal with parenting issues. This study examined which factors are associated with media use for parenting information. Design Cross‐sectional data of 658 parents of children aged 0-8 years, gathered in the CIKEO cohort study in the Netherlands, were analysed. Methods Multivariable logistic regression models were used to examine which factors were associated with media use for parenting information. Results The mean age of the participants was 33.8 years (SD = 5.0); 94.7% were mothers; 77.4% used media for parenting information. Parents with more questions or concerns (OR: 1.40, 95% CI: 1.23, 1.59), and parents who received parenting information from their social contacts (OR: 5.57, 95% CI: 3.22, 9.61), had higher odds of media use for parenting information. Older parents (OR: 0.95, 95% CI: 0.91, 1.00), and parents of older children (OR: 0.84, 95% CI: 0.74, 0.95), had lower odds of media use for parenting information.